Ответы и объяснения

Лучший Ответ!
  • Участник Знаний
2014-03-25T10:35:01+04:00
5X + 2Y = 8 
3X - Y = 7 ( * 2 ) 
6X - 2Y = 14 
_____________
11X = 22 
X = 2 
6 - Y = 7 
Y = 6 - 7 = ( - 1 )
Ответ X = 2  Y = ( - 1 ) 
===========================
X - Y = 5 ---> X = 5 + Y 
XY = 14 
Y*( 5+Y) = 14 
5Y + Y^2 = 14 
______________
Y^2 + 5Y - 14 = 0
D = 25 + 56 = 81 ; V D = 9 
X1 = ( - 5 + 9 ) : 2 = 2 
X2 = ( - 14 ) : 2 = ( - 7 )
______________________
X - Y = 5 
2 - Y1 = 5 ---> Y1 = 2 - 5 = ( - 3 ) 
- 7 - Y2 = 5 ---> Y2 = - 7 - 5 = ( - 12 )
Ответ ( 2 ; - 3 ) ; ( - 7 ; - 12 )